Pengaruh Mobilisasi Saraf Dengan PenambahanDeep Transverse Friction Massage Untuk Mengurangi Nyeri Pada Pasien Carpal Tunnel Syndrome Di Posyandu Lansia Desa Singopuran - Karami, Muhamad Abi, Dwi Rosella Komala Sari, S.Fis., M.Fis. Dipil.Cidesco (2017)
Background: CTS is a disorder of the hand due to the narrowing of the carpal tunnel, either due to edema of the fascia on the tunnel or due to abnormalities in the small bones of the hand so happens emphasis on the median nerve in the wrist CTS is a compressive neuropathy of the upper limb the most frequently encountered and highly disturbing activities of the movement of the hand. Some ways to reduce pain in the CTS is nerve mobilization and deep transverse friction massage. Objective: The aim of this study was to determine whether or not his pengaru 2 difference between nerve mobilization exercises and mobilization of nerves with the addition of transverse friction deep massage to relieve pain in patients with CTS. Methods: The study was quasy eksprimental by means of purposive sampling data retrieval. Data collected were analyzed using the Wilcoxon test and Mann-Whitney test. Results: The results showed the effect of nerve mobilization latiahan to decrease pain in patients with Carpal Tunnel Syndrome (p=0.01), with the addition of nerve mobilization friction deep transverse massage to decrease pain in patients with carpal tunnel syndrome (p=0.005) and different influences between nerve mobilization exercises or mobilization of nerves with the addition of deep transverse friction massage to decrease pain in patients with carpal tunnel syndrome (p=0,005). Conclusion: There is the influence of nerve mobilization exercises with trasverse deep friction massage to relieve pain in patients with carpal tunnel syndrome but occur more significant pain reduction in nerve mobilization group with transverse deep.friction.massage.